Characterization of Vaccine-Enhanced Humoral Immune Responses Against Emergent SARS-CoV-2 Variants in a Convalescent Cohort - Jared Sheehan; Amber J. Trauth; Michael E. Hagensee; Alistair J. Ramsay (Pathogens)
Vaccination of COVID-19–convalescent individuals may generate ‘hybrid’ immunity of enhanced magnitude, durability, and cross-reactive breadth. Our primary goal was to characterize hybrid antibody (Ab) responses in a patient cohort infected with ancestral Wuhan-Hu-1 virus and vaccinated between 6 and 10 months later with the Wuhan-Hu-1–based BNT162b2 mRNA vaccine. We were particularly interested in determining the efficacy of neutralizing Ab responses against subsequently emergent SARS-CoV-2 variants. Sera collected at 3-monthly intervals over a period of 12 months were analyzed by ELISA for SARS-CoV-2 RBD–specific Ab responses, and also for neutralizing Ab activity using pseudovirus-based neutralization assays. We found that convalescent RBD-reactive IgG and IgA Ab responses did not decline significantly through 9 months post-diagnosis. These responses improved significantly following vaccination and remained elevated through at least 12-months. SARS-CoV-2 neutralizing Ab activity was detected in convalescent sera through 9 months post-diagnosis, although it trended downwards from 3 months. Neutralizing Ab activity against the Wuhan-Hu-1 strain was significantly improved by vaccination, to levels that persisted through the end of the study. However, sera collected from vaccinated convalescent subjects also had significant neutralization activity against Delta B.1.617.2 and Omicron variants that persisted for at least 2–3 months, unlike sera from unvaccinated convalescent controls. Thus, vaccination of Wuhan-Hu-1–convalescent individuals with the BNT162b2 vaccine improved and sustained protective neutralizing Ab activity against SARS-CoV-2, including cross-reactive neutralizing activity against variants that emerged months later.